Unraveling recovery : a qualitative study rooted in the lived experiences of persons with complex mental health needs - De Ruysscher, Clara; Vandevelde, Stijn, 1976-; Vanheule, Stijn, 1974- (Gent : Universiteit Gent, 2019)
In dit werk aandacht voor patiënten die niet gebaat zijn bij de standaard dienstverlening maar nood hebben aan heel speciale begeleiding omdat hun noden heel hoog liggen.
A dissertation submitted in partial fulfilment of the requirements for the degree of Doctor of Educational Sciences
Met samenvatting in het Nederlands